JOHN O. HALEY / TOSHIKO TAKENAKA (eds.): Legal Innovations in Asia Judicial Lawmaking and the Influence of Comparative Law - Bälz, Moritz (Zeitschrift für Japanisches Recht, 2016)
Studies in Comparative Law and Legal Culture, Edward Elgar, Cheltenham UK / Northampton, MA USA 2014, 379 pp., 95 £; ISBN: 978 1 78347 278 9